Circuit design and analysis : featuring C routines - Rorabaugh, C. Britton ([Place of publication not identifed] : McGraw Hill Education, 1992)
Professional level software for anyone who designs electrical circuits; the "ready to compile" routines in C language allow the user to configure, customize, and streamline programs more easily and quickly than with software of a wider application.
Circuit design and analysis :, Circuit
Keywords: ELECTRIC FILTERS, DIGITAL -- DESIGN AND CONSTRUCTION -- DATA PROCESSING